Kinerja dan Biaya Aplikasi Herbisida Pratumbuh Menggunakan Drone dan Knapsack Sprayer pada Tebu Plant Cane - Iwan Era Syahputra; Mawar Indah Peranginangin; Fajar Ramadhan (Jurnal Riset Rumpun Ilmu Tanaman, 2026)
Pre-emergence herbicide application in plant cane sugarcane must be completed within a narrow operational window, making work capacity, labor requirement, and unit cost central to method selection. This study compared the operational performance and cost of a drone sprayer and a conventional knapsack sprayer at PT Sinergi Gula Nusantara MKSO Kebun Sei Semayang. A quantitative descriptive-comparative design was applied to 38 operational days during the 2025/2026 planting season, comprising 20 drone days and 18 conventional days. Actual work capacity and labor requirement were tested using the Mann–Whitney U test, while costs were evaluated descriptively through one-way sensitivity and break-even analyses. The drone achieved 10.93 ha/day, approximately 4.03 times the conventional capacity of 2.71 ha/day. Labor requirement was 0.2506 man-days/ha for the drone and 1.3160 man-days/ha for the conventional method. Both differences were significant (p < 0.001) with large effect sizes. Nevertheless, drone application cost IDR 804,043/ha, 5.95% above the conventional cost of IDR 758,908/ha. Cost parity occurred at a drone service tariff of IDR 216,838/ha or a conventional field cost of IDR 252,942/ha. The drone is therefore preferable for time- and labor-constrained operations, whereas the conventional method remains economical under the current cost structure.